Mild Coarctation of Aorta is an Independent Risk Factor for Exercise-Induced Hypertension. Issue 6 (December 2019) - Egbe, Alexander C.; Allison, Thomas G.; Ammash, Naser M.
Abstract : Exercise-induced hypertension is a predictor of cardiovascular events in patients with coarctation of aorta (COA). However, it is unclear whether mild COA diagnosis is an independent risk factor of exercise-induced hypertension. We hypothesized that for every unit increase in exercise, patients with COA (without hemodynamically significant coarctation) will have a higher rise in systolic blood pressure (SBP) compared with matched controls. One hundred forty-nine patients with COA (aortic coarctation peak velocity <2 m/s) who underwent exercise testing were matched 1:1 to controls using propensity score method based on age, sex, body mass index, hypertension diagnosis, and SBP at rest. We compared exercise-induced change in SBP between patients with COA and controls and also assessed the correlation between Doppler-derived aortic vascular function indices (effective arterial elastance index and total arterial compliance index) and exercise-induced changes in SBP. Compared with controls, patients with COA had a greater change in SBP per unit metabolic equivalent (β=2.86; 95% CI, 1.96–4.77 versus 1.07, 95% CI, −0.15 to 1.75; P =0.018) and per unit oxygen pulse (β=4.57; 95% CI, 2.97–7.12 versus 1.45, 95% CI, −0.79 to 2.09, P <0.001). There was a correlation between SBPpeak −SBPrest and elastance index ( r =0.38, P =0.032) and between SBPpeak −SBPrest and total arterial compliance index ( r =−0.51, P =0.001), suggesting an association between vascular dysfunction and exercise-induced BP changes. Patients with COA, without significant obstruction, had higher exercise-induced changes in SBP after adjustment for other risk factors for hypertension. Considering the already known prognostic importance of exercise-induced hypertension, the current study highlights the potential role of exercise testing for risk stratification of patients with mild COA.